Development of radiometric assays for quantification of enzyme activities of the key enzymes of thyroid hormones metabolism - Pavelka, Stanislav (Physiological research, 2014)
We newly elaborated and adapted several radiometric enzyme assays for the determination of activities of the key enzymes engaged in the biosynthesis (thyroid peroxidase, TPO) and metabolic transformations (conjugating enzymes and iodothyronine deiodinases, IDs) of thyroid hormones (THs) in the thyroid gland and in peripheral tissues, especially in white adipose tissue (WAT). We also elaborated novel, reliable radiometric methods for extremely sensitive determination of enzyme activities of IDs of types 1, 2 and 3 in microsomal fractions of different rat and human tissues, as well as in homogenates of cultured mammalian cells. The use of optimized TLC separation of radioactive products from the unconsumed substrates and film-less autoradiography of radiochromatograms, taking advantage of storage phosphor screens, enabled us to determine IDs enzyme activities as low as 10(-18) katals. In studies of the interaction of fluoxetine (Fluox) with the metabolism of THs, we applied adapted radiometric enzyme assays for iodothyronine sulfotransferases (ST) and uridine 5'-diphospho-glucuronyltransferase (UDP-GT). Fluox is the most frequently used representative of a new group of non-tricyclic antidepressant drugs--selective serotonin re-uptake inhibitors. We used the elaborated assays for quantification the effects of Fluox and for the assessment of the degree of potential induction of rat liver ST and/or UDP-GT enzyme activities by Fluox alone or in combination with T(3). Furthermore, we studied possible changes in IDs activities in murine adipose tissue under the conditions that promoted either tissue hypertrophy (obesogenic treatment) or involution (caloric restriction), and in response to leptin, using our newly developed radiometric enzyme assays for IDs. Our results suggest that deiodinase D1 has a functional role in WAT, with D1 possibly being involved in the control of adipose tissue metabolism and/or accumulation of the tissue. Significant positive correlation between specific enzyme activity of D1 in WAT and plasma leptin levels was found. The newly developed and adapted radiometric enzyme assays proved to be very useful tools for studies of factors modulating THs metabolism, not only in model animals but also in clinical studies of human obesity.
Keywords: tuková tkáň; Enzymes; hmotnostní spektrometrie; radiometrie; enzymy; radiofarmaka; lidé; Animals; Adipose Tissue; Radiometry; Mass Spectrometry; Thyroid Hormones; Humans; zvířata; hormony štítné žlázy; Radiopharmaceuticals